Association between obstructive sleep apnea hypopnea syndrome and arteriosclerosis in patients with type 2 diabetes mellitus: mediating effect of blood pressure - Wang, Xinshui; Huang, Xiaolin; Xing, Yuexian; Jiang, Xiaohong; Hua, Fei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to explore the relationship between Obstructive Sleep Apnea Hypopnea Syndrome (OSAHS) and arteriosclerosis in type 2 diabetes mellitus (T2DM) patients and to evaluate the mediating effect of blood pressure in this process.MethodsA total of 411 T2DM patients admitted to the Third Affiliated Hospital of Soochow University from January 2021 to December 2023 were selected and divided into the arteriosclerosis group (n = 299) and the non-arteriosclerosis group (n = 112) based on brachial-ankle pulse wave velocity (ba-PWV). General clinical data, metabolic indicators, and sleep-related parameters were collected. The relationship between the apnea-hypopnea index (AHI) and arteriosclerosis was analyzed using univariable and multivariable logistic regression models, while a generalized additive model (GAM) was applied for curve fitting. A segmented regression model was used to explain nonlinearity, and subgroup analysis was conducted to assess interactions. Finally, a mediation effect model evaluated AHI’s direct and indirect effects on arteriosclerosis.ResultsThe AHI of the arteriosclerosis group was significantly higher than that of the non-arteriosclerosis group (P < 0.001). In the unadjusted, partially adjusted, and fully adjusted regression analyses, elevated AHI significantly increased the risk of arteriosclerosis (P < 0.05). Curve fitting indicated a near-linear positive correlation (P = 0.033). The segmented regression model showed that when AHI < 8.8 events/hour, the risk of arteriosclerosis significantly increased with higher AHI (P = 0.008), but the risk increase was not significant when AHI > 8.8 events/hour (P = 0.124). There was no significant interaction between AHI and blood pressure-related index subgroup indicators (P > 0.05). Mediation analysis revealed that systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) had significant mediating effects on the relationship between AHI and arteriosclerosis (P < 0.05), but the direct effect of AHI on arteriosclerosis was not significant (P > 0.05).ConclusionOSAHS severity elevates arteriosclerosis risk in T2DM patients. Blood pressure is a partial intermediary in this effect.